Maternal Parity, History of Obesity and History of Maternal GDM Risk a Macrosomia Baby - Martanti, Listyaning Eko; Octaviani, Dhita Aulia; Amelia, Rizky; Suparmi, Suparmi; Khobibah, Khobibah (JURNAL INFO KESEHATAN, 2023)
Gestational diabetes mellitus (GDM) is a carbide tolerance disorder that occurs or is first recognized during pregnancy (usually at 24 weeks gestation). For some patients, this complication returns to normal after delivery. The incidence of macrosomic infants or infants weighing >4000 grams is approximately 5% of all births. Maternal GDM is a significant risk factor in the development of fetal macrosomia. This study aimed to determine the risk factors for macrosomia in newborns. The design of this research is cross-sectional design. The population of this study was macrosomic babies born at Dr. Kariadi Semarang from 2015 until 2021. The formula for estimating the sample size using a hypothesis on the mean of two independent populations obtained a total sample of 60 respondents. The sampling technique is convenience sampling. The type of data used is secondary data. This study was analyzed using the Chi-Square test. The results indicated a relationship between parity and a history of obesity and macrosomia incidence in infants with a p-value < 0.05. In contrast, there was no relationship between maternal age, gestational age, and a history of diabetes in the mother and the incidence of macrosomia in infants with a p-value > 0.05. Therefore, it is essential to educate the mother about the risk factors that can cause complications for both the mother and the fetus, including macrosomia.